On the arboreal acarofauna of Hungary: Some new and rare species of prostigmatic mites (Acari: Prostigmata: Tydeidae, Iolinidae and Stigmaeidae) - Ripka, Geza; Laniecka, Izabella; Kazmierski, Andrzej (Zootaxa, 2013)
Eleven arboreal prostigmatic mites from the families Tydeidae, Iolinidae and Stigmaeidae (Prostigmata) are recorded from Hungary. Among them, 8 species are new for science: Tydeus narolicatus Kazmierski and Ripka sp. nov., T. martae Kazmierski sp. nov., T. clavimaculatus Kazmierski sp. nov., Lorryia hungarica Laniecka and Ripka sp. nov., L. sanctikingai Ripka and Laniecka sp. nov., L. bathorii Ripka and Kazmierski sp. nov., Neopronematus solani Laniecka and Kazmierski sp. nov., and Mediolata ronaldi Laniecka sp. nov. Neopronematus lundqvisti Sadeghi et al., 2012 is a new species for fauna of Hungary.